2019
DOI: 10.3389/fonc.2019.00678
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and Effection of MicroRNA-499a in High-Tobacco Exposed Head and Neck Squamous Cell Carcinoma: A Bioinformatic Analysis

Abstract: Background: Few studies have directly investigated the differential expression of microRNAs (miRNAs) in head and neck squamous cell carcinoma (HNSCC) with low, medium, and high tobacco exposure. The purpose of this study is to screen the differentially expressed miRNAs and to investigate their clinical significance and potential biological mechanisms in the three groups of HNSCC. Methods: The datasets of HNSCC were obtained from The Cancer Genome Atlas (TCGA). The edgeR packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Correlation and P-values between the module and clinical characteristics were evaluated by calculating the MEs. In the correlation between the module and clinical characteristics, red represented positive correlation with clinical characteristics, and green represented negative correlation with clinical characteristics (Gong et al, 2019).…”
Section: Identification Of Clinically Significant Modulesmentioning
confidence: 99%
“…Correlation and P-values between the module and clinical characteristics were evaluated by calculating the MEs. In the correlation between the module and clinical characteristics, red represented positive correlation with clinical characteristics, and green represented negative correlation with clinical characteristics (Gong et al, 2019).…”
Section: Identification Of Clinically Significant Modulesmentioning
confidence: 99%
“…The weighed gene co-expression network analysis (WGCNA) algorithm was considered by establishing the scale-free co-expression network to explore the correlation between biologically meaningful gene modules and clinical characteristics ( 14 ). In this study, the R package “WGCNA” was run to calculate Pearson’s correlation matrices and adjacency function of all 309 human AGs.…”
Section: Methodsmentioning
confidence: 99%
“…Gong et al demonstrated that high expression of miR-499a was associated with lower overall survival and N stage in high tobacco exposed HNSCC patients [145].…”
Section: Smoking Tobacco and Alcoholic Beveragementioning
confidence: 99%